Fabrication of wood-inspired high-performance composites through fermentation routes - Dhar P.; Sugimura K.; Yoshioka M.; Yoshinaga A.; Kamitakahara H. (My University, 2025)
In this paper, we developed a microbial route to fabricate wood-inspired biomimetic composites comparable to natural wood. Focusing on the chemical composition of woody biomass, we performed in situ bioprocessing of bacterial cellulose (BC) imbibed in modified cationic lignin (Catlig), which exhibited significant bioactivity in improving the microbial growth dynamics. The structural and morphological characteristics were enhanced by the formation of hydrophobic and electrostatic interactions between BC and Catlig during biosynthesis. Microbially derived BC/Catlig composites exhibited enhanced thermal stability and crystallinity, with oriented cellulose fibers. The tensile properties, toughness, and specific strength of BC/Catlig composites were comparable to those of a heavy wood species (Zelkova serrata) under hydrated conditions and synthetic soft materials. Graphic abstract: [Figure not available: see fulltext.] © 2021, The Author(s), under exclusive licence to Springer Nature B.V.